2007
DOI: 10.1111/j.1399-3054.2007.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐induced changes in the redox state of the cytochrome b559 in photosystem II depend on the integrity of the Mn cluster

Abstract: The effect of oxygen and anaerobiosis on the redox properties of Cyt b(559) was investigated in PSII preparations from spinach with different degree of disintegration of the donor side. Comparative studies were performed on intact PSII membranes and PSII membranes that were deprived of the 18-kDa peripheral subunit (0.25 NaCl washed), the 18- and 24-kDa peripheral subunits (1 M NaCl washed), the 18-, 24- and 33-kDa peripheral subunits (1.2 M CaCl(2) washed), Cl depleted and after complete depletion of the Mn c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The Mn 4 CaO 5 cluster and extrinsic subunits were removed by the Tris washing (Gadjieva et al 1999 , Mamedov et al 2007 ). PS II membranes were resuspended in 1.0 M Tris buffer at pH 9.1 with Chl concentration 1 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mn 4 CaO 5 cluster and extrinsic subunits were removed by the Tris washing (Gadjieva et al 1999 , Mamedov et al 2007 ). PS II membranes were resuspended in 1.0 M Tris buffer at pH 9.1 with Chl concentration 1 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The slow oxidation behavior of Tyr D makes it possible to study by the conventional EPR spectroscopy while Tyr Z oxidation kinetics is too fast to be followed. Different biochemical treatment such as Tris and NH 2 OH washing can remove the Mn 4 CaO 5 cluster and extrinsic proteins, leaving PS II core exposed to the lumen (Boussac and Etienne 1982b ; Gadjieva et al 1999 ; Mamedov et al 2007 ). This makes Tyr Z oxidation to slow down by two or three orders of magnitude (t 1/2 = 20–600 ms) (Buser et al 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…The S 2 state multiline EPR signal from the CaMn 4 cluster was induced by illumination at 200 K for 6 min (23). The total manganese content in the samples, measured at room temperature, was estimated after extraction with 200 mM HNO 3 and 100 mM CaCl 2 as described previously (37). Spectral analysis was performed using Bruker Xepr 2.1 software.…”
mentioning
confidence: 99%
“…pH changes or photoinhibitory conditions. It has also been shown recently that the different potential forms of cyt b559 are interconvertible in Tris‐treated PSII membranes in an O 2 ‐dependent manner (Mamedov et al 2007). Tiwari and Pospisil (2009) showed that cyt b559 is converted by O 2 − after tens of seconds illumination from the intermediate into the high potential form and then, after longer illumination (more than 100 s) in a lower potential form.…”
Section: Discussionmentioning
confidence: 99%